Experimental rewilding may restore abandoned wood-pastures if policy allows - Garrido, Pablo (Ambio, 2020)
Large herbivores play key roles in terrestrial ecosystems. Continuous defaunation processes have produced cascade effects on plant community composition, vegetation structure, and even climate. Wood-pastures were created by traditional management practices that have maintained open structures and biodiversity for millennia. In Europe, despite the broad recognition of their biological importance, such landscapes are declining due to land-use changes. This calls for finding urgent solutions for wood-pasture conservation. To test whether introducing an ecological replacement of an extinct wild horse could have positive effects on wood-pasture restoration, we designed a 3-year rewilding experiment. Horses created a more open wood-pasture structure by browsing on seedlings and saplings, affected tree composition via selective browsing and controlled the colonization of woody vegetation in grassland-dominated areas. Thus, rewilding could be a potential avenue for wood-pasture restoration and biodiversity conservation. However, such benefits may not materialize without a necessary paradigm and political shift. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-020-01320-0) contains supplementary material, which is available to authorized users.